Prevalence of Microvolt T-Wave Alternans in Patients With Long QT Syndrome and Its Association With Torsade de Pointes. (February 2016) - Takasugi, Nobuhiro; Goto, Hiroko; Takasugi, Mieko; Verrier, Richard L.; Kuwahara, Takashi; Kubota, Tomoki; Toyoshi, Hiroyuki; Nakashima, Takashi; Kawasaki, Masanori; Nishigaki, Kazuhiko; Minatoguchi, Shinya
Abstract : Background—: Prevalence of microvolt T-wave alternans (TWA) and the strength of its association with torsade de pointes (TdP) history have not been fully investigated in patients with long QT syndrome (LQTS). Methods and Results—: Twenty-four–hour continuous 12-lead ECGs were recorded in 10 healthy subjects (5 men; median age, 21.5 years) and 32 patients (13 men; median age, 13 years) with LQTS types 1 (n=18), 2 (n=4), 3 (n=4), and unidentified (n=6). Peak TWA was determined by the Modified Moving Average method. None of the healthy subjects had TWA ≥42 µV. All 8 (100%) LQTS patients with a history of TdP exhibited TWA ≥42 µV, whereas only 14 (58.3%) of the 24 LQTS patients without TdP history reached ≥42 µV (p=0.04). Thus, the 42-µV cut point provided 100% sensitivity and 41.7% specificity for an association with TdP history. In the 22 (68.8%) LQTS patients with TWA ≥42 µV, only 2 (median; interquartile range, 1–3) leads exhibited TWA ≥42 µV. Highest TWA levels were recorded in precordial leads (V1 –V6 ) in 30 (93.8%) patients, most frequently in lead V2 (43.8%). A single ECG lead detected only ⩽63.6% of TWA ≥42 µV episodes, whereas the combined leads V2 to V5 detected 100% of TWA ≥42 µV. Conclusions—: Microvolt TWA is far more prevalent in LQTS patients than previously reported and is strongly associated with TdP history. TWA should be monitored from precordial leads in LQTS patients. The use of a limited set of ECG leads in conventional monitoring has led to underestimation of TWA and its association with TdP.